2018
DOI: 10.1111/cns.12836
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and service engagement in major depressive disorder with psychotic features: comparisons with schizophrenia, schizoaffective disorder and bipolar disorder in a 6‐year follow‐up of the Cavan‐Monaghan First Episode Psychosis Study (CAMFEPS)

Abstract: At 6-year follow-up, these diagnoses are characterized by quantitative rather than qualitative differences in psychopathology, functionality, quality of life, and service engagement, with considerable overlap between them. These findings suggest that MDDP should join SZ, SA, and BD in a milieu of psychosis that transcends arbitrary boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…People with serious mental illness (PSMI) experience problems functioning independently within the community, showing social and occupational limitations. Several authors have stated that the deficit in psychosocial functioning of PSMI includes anhedonia, few interpersonal contacts, lack of social participation and/or poor social support (Kingston et al., 2018; Sweet et al., 2018). The explanation for this poor social adjustment in PSMI involves a complex and dynamic interaction between several clinical and sociocultural factors, such as the level and the type of clinical symptomatology, house conditions, low income or stigma (Killaspy et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…People with serious mental illness (PSMI) experience problems functioning independently within the community, showing social and occupational limitations. Several authors have stated that the deficit in psychosocial functioning of PSMI includes anhedonia, few interpersonal contacts, lack of social participation and/or poor social support (Kingston et al., 2018; Sweet et al., 2018). The explanation for this poor social adjustment in PSMI involves a complex and dynamic interaction between several clinical and sociocultural factors, such as the level and the type of clinical symptomatology, house conditions, low income or stigma (Killaspy et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of engagement in treatment among those with mental health di culties is a signi cant problem [18]. Previous research indicates that at an individual level, factors such as male sex, younger age, greater severity of illness, diminished functional capacity, having a diagnosis of schizophrenia or schizoaffective disorder [19][20][21][22][23][24][25] and comorbid mental health and substance use conditions [22,25] are associated with higher rates of attrition and disengagement from mental health services. Perceptions about the e cacy of treatment [25] as well as the quality of the interactions between clients and providers [25,26] can also inform decisions about whether or not to engage.…”
Section: Introductionmentioning
confidence: 99%
“…So far none of these mental health-related studies during COVID-19, took the role or potential in uence of one's daily meaningful activities on adults' mental health into account, although the lockdown had a major impact on persons daily activities [29]. Notwithstanding, previous research showed that daily activities can have a huge impact on one's mental health [30][31][32][33][34][35].…”
mentioning
confidence: 99%